A pinch of tradition assessing the dynamics of the salt heritage in Malolos City, Bulacan - Panganiban, Julianne R.; Parrera, Lorrain H.
This study investigated salt's production, marketing, and profitability in the City of Malolos, Bulacan. It aimed to: (1) identify the participants in the production and marketing of salt and the utilities they create; (2) ascertain the profitability of salt farming; (3) determine the marketing channel of salt; and (4) discuss the problems being faced by the participants. The study used the theory of the firm and the institutional approach to the study of marketing as elements of its framework. The needed data for the study were gathered through face-to-face interviews of eighteen (18) salt farmers. The study found that the salt industry in Malolos, characterized by a patriarchal structure, is encountering difficulties due to an aging workforce. It identified six key players in the production and marketing of salt: suppliers, salt makers, agents (inkargados), traders(biyaheros), wholesalers, and retailers, with significant marketing margins justified by the creation of form, place, time, and possession utilities, respectively. The study highlights two management systems: the Kasama and Buwisan systems. Salt farming is a profitable enterprise, generating annual profits ranging from P80,000 to more than P100,000 with a profit margin of approximately 30%. Nearly 100% of the salt produced in Malolos is sold to wholesalers throughout Central Luzon, South Luzon, and Metro Manila. However, salt makers face problems including climate change, low technological adoption, meager income, ASIN Law's passage, importation, urbanization, lack of government support, health risks, and low skill transfer. The study concludes the without intervention, the salt industry is at risk of extinction. The study recommends that (1) salt farmers will benefit from joining cooperatives, (2) the Bulacan local government should boost funding for subsidies and upskilling programs, and (3) the National Government should strengthen research and development efforts while implementing more stringent policies to safeguard the salt industry.